Desempeño laboral de la empresa comercial Dismero S.A - Diaz Sanchez, Karen Eugenia (2019)
For companies dedicated to the commercialization of products of first necessity, it is essential to have human talent trained in customer service skills, and certain management skills, which allow a proper development of activities within the institution, so that infers that job performance is the individual performance that each member of the company has, that is, it is the action that the worker manifests in the workplace, and that influences individual productivity, in conjunction with the company's short-term goals